Decision Making Processes for a Patient with Cardiac Pacemaker Admitted to the Accident and Emergency Undergoing Magnetic Resonance Imaging – A Case Study - F. P. Raditya (ASEAN Journal on Science and Technology for Development, 2015)
This case study aims to apply the processes of decision-making for magnetic resonance imaging (MRI) as a diagnostic examination for a patient with cardiac pacemaker admitted to a private hospital in the capital of Indonesia. It also aims to examine and evaluate the case of a 53-year-old mother who had a heart abnormality that has a pacemaker for one year and was diagnosed to do an MRI examination because of a suspected tumor on the wrist area.The three basic models of decision-making — the descriptive, prescriptive and normative — were applied. The prescriptive used the information processing theory, while the normative used decision trees as decision options and lastly, the descriptive used intuition and pattern recognition.Dominantly, the prescriptive model for decision-making is more appropriate for this case.  The descriptive decision-making model, using intuition however, helped in supporting the intuitive hypothesis.  Lastly, the normative model of decision-making played an important role but was not likely effective.